Segmental and phonological aspects in the analysis of early speech : the use of a computer - based program - Kyprianou, Anna (Τμήμα Επιστημών Αποκατάστασης, Σχολή Επιστημών Υγείας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2019)
This research supports the collection of linguistic data from children aged around 3-6 years old. In particular, children were presented with images and were asked to name them in order to record the profiles of their vocal and phonological features. The present study used two types of analysis. The first type concerns the independent analysis where the diversity of the vocal profile of each child is investigated in order to explore which sounds are produced independently of the adult’s model. The second type of analysis examines the phonological field of the child that includes the process of how children use the voices and how they determine them in the level of a word or even in spontaneous speech. Moreover, the phonological profile with the production pattern and any processes that are most relevant to the deletion of the syllable at the beginning of the word, the advanced remote assimilation of the syllable intervention at the beginning of the word and the proper production of the syllable spelling at the beginning of the word, are examined. Furthermore, the data was processed by an excel macro which analyzes the speech in phonological processes. The purpose of the research is the pilot implementation of the LOGOS therapy (Linguistic Growth of Speech Outcomes) and is considered pioneering, because no such tool has been developed to help analyze a rapid and targeted development of a phonological pattern of a child, which extends beyond the articular pattern. The software program of the research gives an indication of both the vocal and the phonological ability of the child in selected parameters related to the dialect and the language of a child.
Keywords: Phonological Processes; Assessment of Speech Production; Cypriot Greek Dialect; Computer Assisted Analyses